1977
DOI: 10.1007/bf01405393
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic contribution to the problem of enlargement of cerebral arteriovenous malformations

Abstract: From a series of 325 cases of cerebral arteriovenous malformations, seven patients are reported presenting a change in size of the malformation in the course of several years. The enlargement of the malformation is documented by four vessel cerebral angiography, and haemodynamic and histopathological characteristics are discussed. Serial four vessel cerebral angiography is strongly indicated for accurate diagnosis, and radical excision of these malformations with the microtechnical method is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The initial hypothesis of the congenital origin and growth tendency of AVMs is presently a matter of debate. Enlargement of AVMs or regrowth after negative postoperative angiograms argue for AVMs as dynamic lesions [6,7,8,9,11,12,13,15,26,27]. These observations are supported by several immunohistochemical studies demonstrating the involvement of angiogenic factors.…”
Section: Discussionsupporting
confidence: 68%
“…The initial hypothesis of the congenital origin and growth tendency of AVMs is presently a matter of debate. Enlargement of AVMs or regrowth after negative postoperative angiograms argue for AVMs as dynamic lesions [6,7,8,9,11,12,13,15,26,27]. These observations are supported by several immunohistochemical studies demonstrating the involvement of angiogenic factors.…”
Section: Discussionsupporting
confidence: 68%
“…Unfortunately, although the clinical risks of untreated AVMs are well documented, the angiographic natural history is less well known. Reports of serial angiography in patients with untreated AVMs are mostly limited to case reports of 1 or 2 patients [1, 2, 8], and the few series have small numbers [3, 6, 24, 33]. In total, we identified only 48 cases with delayed angiography at least 1 year after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these cases with coincidental imaging prior to diagnosis of an AVM, there are numerous cases, including the first 3 presented here, in which no AVM is evident on angiography and then abnormal nidus vessels subsequently appear [1, 3, 21, 22,24,25,26,27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…18,24,27,47,64,72,75,76,80,81,85,86,90,112,116,118 One series of 106 patients with AVMs has demonstrated that > 50% of the lesions increased in size, whereas 9% decreased over a mean period of 8 years without intervention. Remodeling within these lesions can lead to changes in their angiographic appearance over time.…”
mentioning
confidence: 99%